The Relationship between Emotional Intelligence and Work Stress among Healthcare Workers at Kawatuna Public Health Center, Palu City - Ashari, Muhammad Rizki; Arwan, Arwan; Sarungallo, Amelia Tirsa (Public Health of Indonesia, 2025)
Background: Work-related stress remains a major concern among healthcare professionals, significantly affecting their mental, physical, and psychological well-being. Emotional intelligence is recognized as a crucial factor that can influence how individuals experience and manage occupational stress. At the Kawatuna Public Health Center in Palu City, healthcare workers are frequently exposed to stressors such as time pressure, high job responsibility, inadequate work environments, and demanding patient characteristics. These stressors can lead to emotional disturbances, including increased sensitivity, emotional detachment, and reduced motivation. Objectives: This study aimed to examine the relationship between emotional intelligence encompassing self-awareness, self-regulation, self-motivation, empathy, and social skills and work-related stress among healthcare workers at the Kawatuna Public Health Center. Methods: This was a quantitative study using a cross-sectional analytic survey design. Total sampling was applied, involving 40 eligible respondents. Data were collected using structured questionnaires: a Likert-scale emotional intelligence instrument and the WHO DASS questionnaire to assess work-related stress. Data analysis was performed using the Chi-Square test. Results: To revealed significant associations between emotional intelligence components and work-related stress: self-awareness (p = 0.001), self-regulation (p = 0.001), self-motivation (p = 0.031), empathy (p = 0.020), and social skills (p = 0.012). Higher emotional intelligence was associated with lower stress levels. Conclusion: Enhancing emotional intelligence through training and psychological support can be a valuable strategy in reducing work-related stress among healthcare workers. Keywords: emotional intelligence; work-related stress; healthcare workers; public health center